Two different short fiber-reinforced resin composites for extensive MOD cavities in premolars and molars - Oksanen, Viivi; Bijelic-Donova; Jasmina; Vallittu; Pekka K.; Lassila, Lippo; Garoushi, Sufyan (Springer Nature, 2026)
Objectives
To assess the influence of (1) incorporating micro- and millimeter-scale short fiber-reinforced composite (SFC) on the fracture behavior of large direct restorations made in premolars (P) and molars (M); (2) tooth size on the fracture resistance and their correlation.
Materials and methods
Wide MOD cavities with missing lingual walls were prepared in premolars and molars. Four groups were designed (n = 15/group). Teeth in PFC group were restored with particulate filler resin composite (Gaenial Universal Injectable) without fiber reinforcement. Teeth in bilayered group were made of micrometer-scale SFC-core (everX Flow) veneered with a resin composite layer 1 mm in thickness. Monolithic SFC restorations were made either with plain SFC (everX Flow) or with plain hybrid SFC. The hybrid SFC was composed of handmade mixture of micro- and millimeter-scale SFCs (everX Flow and everX Posterior). Specimens were stored in water for 12 months before quasi-static loading. Fractures were analyzed using scanning electron microscopy. Data were statistically analyzed with two-way ANOVA (p = 0.05), followed by the Tukey HSD test. Additionally, Pearson correlation analyses (p = 0.001) were conducted.
Results
Restorations in premolars exhibited statistically significant lower fracture resistance than those in molars, except for the plain SFC group (p < 0.05;r = 0.0114) (PFC P 481 ± 159 N; PFC M 1221 ± 435 N; Bilayered P 727 ± 387 N; Bilayerd M 1954 ± 517 N; SFC P 1735 ± 533 N; SFC M 1847 ± 551 N; SFC-hybrid P 1485 ± 339 N; SFC-hybrid M 2280 ± 375 N). In both, premolars and molars, the application of SFC as core or plain restorative material demonstrated superior fracture endurance compared to PFC restorations. Hybrid SFC in molars displayed significantly higher fracture resistance (p < 0.05) compared to the other groups. Pearson correlation indicated statistically significant positive correlation in favor of molars (p < 0.001;r = 0.490) (PFC r = 0.712, Bilayered r = 0.815, SFC-hybrid r = 0.767), except for the plain SFC group (r = 0.114).
Conclusions
The volume and consistency of SFC significantly impact the fracture endurance and fracture mode of direct composite restorations.
Clinical significance
Tooth and short fiber reinforced composite (SFC) type are factors that should be taken into account when planning the SFC restoration. Molars could be restored with any type of SFC, however gaining a high volume of plain flowable or preferably hybrid SFC in premolars is highly important.